Kelvin and Rossby Wave Contributions to the Mechanisms of the Madden–Julian Oscillation - Patrick Haertel (Geosciences, 2022)
The Madden–Julian Oscillation (MJO) is a large-scale tropical weather system that generates heavy rainfall over the equatorial Indian and western Pacific Oceans on a 40–50 day cycle. Its circulation propagates eastward around the entire world and impacts tropical cyclone genesis, monsoon onset, and mid-latitude flooding. This study examines the mechanism of the MJO in the Lagrangian atmospheric model (LAM), which has been shown to simulate the MJO accurately, and which predicts that MJO circulations will intensify as oceans warm. The LAM MJO’s first baroclinic circulation is projected onto a Kelvin wave leaving a residual that closely resembles a Rossby wave. The contribution of each wave type to moisture and moist enthalpy budgets is assessed. While the vertical advection of moisture by the Kelvin wave accounts for most of the MJO’s precipitation, this wave also exports a large amount of dry static energy, so that in total, it reduces the column integrated moist enthalpy during periods of heavy precipitation. In contrast, the Rossby wave’s horizontal circulation builds up moisture prior to the most intense convection, and its surface wind perturbations enhance evaporation near the center of MJO convection. Surface fluxes associated with the Kelvin wave help to maintain its circulation outside of the MJO’s convectively active region.